Indonesia's Joins BRICS: Balancing Economic Opportunities and Geopolitical Challenges in a Multipolar World - Asep Setiawan (Dinasti Research, 2025)
This study explores Indonesia’s interest in joining BRICS (Brazil, Russia, India, China, and South Africa) and evaluates the economic, geopolitical, and strategic implications of its potential membership. Employing a qualitative methodology, the study examines Indonesia’s motivations for aligning with BRICS and assesses the challenges of maintaining balanced foreign relations with both BRICS nations and Western allies. The findings indicate that Indonesia views BRICS membership as a means to diversify economic partnerships, access alternative financial mechanisms, and enhance its influence in global governance. However, membership also poses risks, including potential diplomatic tensions with Western powers and challenges to Indonesia’s traditional “bebas aktif” (independent and active) foreign policy. The study further explores the regional implications of Indonesia’s BRICS membership, particularly in ASEAN, and considers whether Indonesia could serve as a diplomatic bridge between BRICS and Western-led institutions. While BRICS offers Indonesia economic and political opportunities, the study highlights the complexities of navigating global power shifts in an increasingly multipolar world. Ultimately, Indonesia's decision on BRICS membership will reflect its broader strategy for balancing national interests, economic pragmatism, and geopolitical alignment in a rapidly evolving global order.